Mathematical model of sapphire micromachining by CVD diamond coating tool. Issue 200 (24th July 2019) - Wanshan, Tian; Shouxin, Yu; Jing, Pang; Wei, Liu; Dunwen, Zuo; Wenzhuang, Lu
Abstract: A CVD diamond coating tool with prismatic crystal structure was prepared by hot filament chemical vapor deposition (HFCVD) method to improve sapphire's lapping efficiency. The full plastic removal model of Sapphire (0001) plane is established based on the extended domain removal theory of hard and brittle materials such as sapphires. This model is used to analyze the effect of parameters such as prismatic particle's size of the CVD diamond coating, lapping rate, lapping pressure, and material properties on the removal rate during the lapping process, and to predict the material removal rate, which lays the foundation for the high-efficiency micromachining of sapphire.